Prevalence of borrowing and sharing prescription medicines and associated socio-demographic factors: findings from COBERS health centres in northern Uganda - Obol, James Henry (BMC Pharmacol Toxicol, 2018)
BACKGROUND: The use of prescription medications without the involvement of medical professionals is a growing public health concern. Therefore this study was conducted to determine the prevalence of borrowing and sharing prescription medicines and associated socio-demographic factors among community members who had sought health care from COBERS health centres. METHODS: We conducted analytical cross – sectional study among former patients who sought treatment during the two months period prior to data collection in nine COBERS health centres. We used cluster proportional-to-size sampling method to get the numbers of research participants to be selected for interview from each COBERS site and logistic regression model was used to assess the associations. RESULTS: The prevalence of borrowing prescription medication was found to be 35.9% (95% CI 33.5–38.2%) and sharing prescription medication was 32.7% (95% CI 30.4–34.9%). The Socio-demographic factors associated with borrowing prescription medicines were: age group ≤19 years (AOR = 2.64, 95%CI 1.47–4.74, p-value = 0.001); age group 20–29 years (AOR = 2.78, 95%CI 1.71–4.50, p-value≤0.001); age group 30–39 years (AOR = 1.90, 95%CI 1.18–3.06, p-value = 0.009); age group 40–49 (AOR = 1.83, 95%CI 1.15–2.92, p-value = 0.011); being a female (AOR = 2.01, 1.58–2.55, p-value< 0.001); being a Pentecostal by faith (AOR = 1.69, 95%CI 1.02–2.81, p-value = 0.042) and being Employed Salary Earner (AOR = 0.44, 95%CI 0.25–0.78, p-value = 0.005). The socio-demographic factors associated with sharing prescription medicines were: age group ≥19 years (AOR = 4.17, 95%CI 2.24–7.76, p-value< 0.001); age group 20–29 years (AOR = 3.91, 95%CI 2.46–6.29, p-value< 0.001); age group 30–39 years (AOR = 2.94, 95%CI 2.05–4.21, p-value< 0.001); age group 40–49 years (AOR = 2.22, 95%CI 1.29–3.82, p-value = 0.004); being female (AOR = 2.50, 95%CI 1.70–3.47, p-value< 0.001); being Pentecostal by faith (AOR = 2.15, 95%CI 1.15–4.03, p-value = 0.017); and being engaged in business (AOR = 1.80, 95%CI 1.16–2.80, p-value = 0.009). CONCLUSION: A high proportion of study participants had borrowed or shared prescription medicines during the two months prior to our study. It is recommended that stakeholders sensitise the community members on the danger of borrowing and sharing prescription medicines to avert the practice. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s40360-018-0206-5) contains supplementary material, which is available to authorized users.